Observations of continental biogenic impacts on marine aerosol and clouds off the coast of California. Issue 11 (11th June 2014) - Coggon, M. M.; Sorooshian, A.; Wang, Z.; Craven, J. S.; Metcalf, A. R.; Lin, J. J.; Nenes, A.; Jonsson, H. H.; Flagan, R. C.; Seinfeld, J. H.
Abstract During the 2011 Eastern Pacific Emitted Aerosol Cloud Experiment (E‐PEACE) and 2013 Nucleation in California Experiment (NiCE) field campaigns, a predominantly organic aerosol (> 85% by mass) was observed in the free troposphere over marine stratocumulus off the coast of California. These particles originated from a densely forested region in the Northwestern United States. The organic mass spectrum resolved by positive matrix factorization is consistent with the mass spectra of previously measured biogenic organic aerosol. Particulate organic mass exhibits a latitudinal gradient that corresponds to the geographical distribution of vegetation density and composition, with the highest concentration over regions impacted by densely populated monoterpene sources. Due to meteorological conditions during summer months, cloud‐clearing events transport aerosol from the Northwestern United States into the free troposphere above marine stratocumulus. Based on the variation of meteorological variables with altitude, dry air containing enhanced biogenic organic aerosol is shown to entrain into the marine boundary layer. Fresh impacts on cloud water composition are observed north of San Francisco, CA which is consistent with fresh continental impacts on the marine atmosphere at higher latitudes. Continental aerosol size distributions are bimodal. Particles in the 100 nm mode are impacted by biogenic sources, while particles in the ∼ 30 nm mode may originate from fresh biogenic emissions. Continental aerosol in the 100 nm mode is cloud condensation nuclei active and may play a role in modulating marine stratocumulus microphysics.